The Effect Of Good Corporate Governance And Political Connection On Firm Value (Case Study On Manufacturing Companies Listed On The Indonesia Stock Exchange 2015-2020) - Mellia Fitriana; Ade Imam Muslim (Kompartemen : Jurnal Ilmiah Akuntansi, 2022)
This study aims to determine how the influence of good corporate governance and political connections on firm value. To Answer our reserach question, we use 342 observations from manufacturing companies listed on the Indonesian Stock Exchange and multiple regression method. The results of this study indicate that simultaneously good corporate governance and political connection have a significant effect on firm value with a significance level of 0,05. Partially, good corporate governance as proxied by institutional ownership has no effect on firm value. Independent Commissioner has a significant effect on firm value. The Audit Committee has no effect on the value of the company. Partially, Political Connections has no effect on the value of the company. Partially, firm size has no effect on firm value. And partially ROA has an effect on firm value with a significance level of 0,05.